Binder as well as preparation method and application thereof

The new binder produced by copolymerization of tarragon and amide monomers solves the problem of insufficient fixation capacity of silicon-based negative electrode materials in lithium-ion batteries, improves the cycling and dynamic performance of the battery, and reduces bonding Dosage.

CN119220201APending Publication Date: 2024-12-31SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619009.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

After long-term reuse of the binder in existing lithium-ion batteries, the fixing capacity of the silicon-based negative electrode material is insufficient, resulting in the powdering and falling off of the active substance, affecting the battery capacity and cycle life.

Method used

A new type of binder prepared by copolymerization reaction between tarragon and amide monomer under the initiation of initiator provides more binding points and ion transport capabilities through polyhydroxyl groups and polyether groups to form a dense protective layer. Constrain the displacement and fragmentation of active substances.

Benefits of technology

The bonding strength of the adhesive is improved, the expansion force and crushing degree of the negative electrode material are suppressed, the circulation and kinetic properties of the battery are extended, and the amount of total adhesive is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220201A_ABST
    Figure CN119220201A_ABST
Patent Text Reader

Abstract

The invention discloses a binder and a preparation method and application thereof, and relates to the technical field of lithium ion batteries, and the binder is a purified tara gum or a composition prepared by carrying out a copolymerization reaction on the purified tara gum and an amide monomer under the initiation of an initiator. The binder is prepared from the following raw materials in parts by mass: 3 to 5 parts of purified tara gum, 18 to 22 parts of amide monomer, 5 to 8 parts of initiator and 480 to 520 parts of precipitator. Due to the existence of polyhydroxy groups and polyether groups of the tara gum, more sites and ion transmission capability are provided; and meanwhile, the polyhydroxy action of the tara gum provides more binding points of force, so that a more compact protective layer is formed, the displacement and fragmentation trend of active substances are restrained, and the cycle performance of the battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a binder, a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have become the first choice for modern energy storage solutions due to their advantages such as long life, design flexibility and portability. In lithium-ion electrodes, binders play a vital role. They are not only responsible for closely connecting active materials, conductive agents and current collectors, but also maintain the stability of the entire electrode structure, ensuring the formation of a continuous and complete conductive network, thereby ensuring that the battery can operate efficiently and stably.

[0003] Currently, for the application of silicon-based negative electrode materials, several common types of binders on the market include sodium alginate (SA), sodium carboxymethyl cellulose (CMC-Na) and polyacrylic acid (PAA). Among them, PAA and SA are known for their good interfacial adhesion properties. However, these linear polymers are prone to displacement or sliding when faced with high mechanical stress, especially during the expansion and contraction of silicon particles. This instability may cause the internal structure of the electrode to gradually disintegrate, thereby affecting the battery cycle life and performance.

[0004] To overcome the above challenges, researchers have explored a range of new composite adhesive solutions, such as: Chinese patent CN113851653A discloses a modified natural binder for lithium-ion batteries, wherein the binder is guar gum grafted with polyacrylamide (GG-g-PAM), that is, a modified binder of guar gum and acrylic acid.

[0005] Chinese patent CN108232109A discloses a method for preparing a silicon-based negative electrode plate for a lithium-ion battery, wherein the binder is konjac glucomannan.

[0006] Chinese patent CN112133916A discloses a lithium-ion battery silicon-based negative electrode material binder and its preparation method and application, which is a binder obtained by copolymerizing sodium alginate and polyacrylamide.

[0007] Chinese patent CN114142040A discloses a lithium battery negative electrode silicon-based material binder, which is a binder obtained by kneading together commonly used binders such as konjac gum-acrylic acid graft copolymer, guar gum, sodium alginate, and terminal hydroxyl polybutadiene.

[0008] Despite this, these binders developed under existing technical conditions still have certain limitations, especially after long-term cyclic use, their ability to fix silicon-based negative electrode materials is insufficient, which can easily cause the active substances to pulverize and fall off from the electrode, thereby causing rapid decay of battery capacity.

[0009] Therefore, the development of new binders that are more durable and can effectively suppress the negative effects of the expansion force and crushing degree of negative electrode materials remains one of the key issues that need to be urgently addressed in the field of lithium-ion batteries. Summary of the invention

[0010] The technical problem to be solved by the present invention is how to improve the bonding strength of the binder, thereby suppressing the expansion force and crushing degree of the negative electrode material, and further improving the cycle performance of the silicon-based negative electrode.

[0011] In order to solve the above technical problems, the present invention provides a binder, which is applied to lithium-ion batteries, and the raw material of the binder is tara gum.

[0012] Optionally, the binder is prepared by copolymerization of tara gum and amide monomers under the initiation of an initiator.

[0013] Furthermore, based on the mass parts of the raw materials for preparing the binder, the raw materials of the compound include 3-5 parts of tara gum, 18-22 parts of amide monomers, 5-8 parts of initiators and 480-520 parts of precipitants.

[0014] Optionally, the amide monomer is one or more of acrylamide, bisolefin amide, and polyether-polyacrylamide.

[0015] Optionally, the initiator is one or more of ammonium cerium nitrate and benzoyl peroxide.

[0016] Optionally, the precipitant is one or more of anhydrous ethanol, isopropanol, acetone, and ethyl acetate.

[0017] Optionally, the binder further includes a solvent, and the solvent is one or more of deionized water, benzyl acetate, hexyl butyrate, toluene, xylene, isobutyl isobutyrate, and butyl butyrate.

[0018] According to another aspect of the present invention, the preparation method of the binder comprises the following steps: S1. Take purified tara gum to obtain binder A; S2, preparing the binder A into a first solution, mixing it with the amide monomer to carry out graft copolymerization reaction, and obtaining a second solution; S3, adding the initiator dropwise into the second solution at a rate of up to 5 mL / min to obtain a third solution; S4. Adding the precipitant to the third solution to obtain a solid product, washing and drying the solid product to obtain the binder.

[0019] Furthermore, S3 further comprises placing the solution after the initiator has been dripped in a 40-50° C. water bath to react for 10-14 hours.

[0020] Furthermore, the purified tara gum is obtained by extraction, and the extractant used in the extraction is one or more of anhydrous ethanol, methanol or isopropanol.

[0021] Furthermore, the step of adding the precipitant to the third solution to obtain a solid product further comprises: adding the precipitant into the third solution to extract the synthetic product, so as to leave the synthetic product in the precipitant layer; The extractant was removed using a rotary evaporator to obtain the solid product.

[0022] A negative electrode slurry comprises a negative electrode active material, a conductive agent and the above-mentioned binder.

[0023] Furthermore, it also includes silicon dioxide or silicon carbon powder, CMC (2% glue), wherein: The mass ratio of the negative electrode active material, the silicon oxide or silicon carbon powder, the conductive agent, the CMC (2% glue solution), and the binder is (89.09-95.8): (5.27-6.71): 1.5: 0.5: 2.2.

[0024] According to another aspect of the present invention, a negative electrode plate is provided. The negative electrode plate is made of a current collector and the negative electrode slurry loaded on the current collector.

[0025] According to another aspect of the present invention, a lithium-ion battery includes a positive electrode sheet and the negative electrode sheet.

[0026] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: Due to the presence of polyhydroxyl and polyether groups in tara gum, more sites and ion transmission capabilities are provided; at the same time, the polyhydroxyl effect of tara gum provides more force binding points, forming a denser protective layer, restraining the displacement and fragmentation tendency of the active substance, and improving the cycle performance of the battery cell; in addition, since the binder provided by the present invention increases the binding force and provides strong peeling force, the total amount of binder can be reduced on the original basis, thereby better improving the dynamic performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 is the structural formula of tara gum in the present invention; Figure 2 is the structural formula of acrylamide in the present invention; Figure 3 is the structural formula of the binder in the present invention. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0031] Glossary: CMC: sodium carboxymethyl cellulose; SBR: styrene butadiene rubber; FEC additive: Fluoroethylene carbonate is a common electrolyte additive.

[0032] The first aspect of the present invention is to provide a binder with high bonding strength, which is applied to lithium-ion batteries to suppress the expansion force and crushing degree of silicon-based negative electrode materials and improve the cycle performance of silicon-based negative electrodes.

[0033] The binder provided by the present invention is purified tara gum, which is referred to as binder A.

[0034] See also Figure 1 The tara gum structure shown in the figure provides more sites and ion transmission capabilities due to the presence of polyhydroxyl and polyether groups in tara gum. At the same time, the polyhydroxyl group of tara gum provides more force binding points, forming a denser protective layer, restraining the displacement and fragmentation tendency of the active substances, and improving the cycle performance of the battery cell. In addition, since the binding force is improved and a strong peeling force is provided, the total amount of binder can be reduced on the original basis, thereby better improving the dynamic performance of the battery cell.

[0035] See also Figure 3The structural formula of the compound shown in FIG. 1 is a binder provided by the present invention, which is a compound prepared by copolymerization of purified tara gum and amide monomers under the initiation of an initiator, and is recorded as binder B.

[0036] In a further embodiment, the binder includes 3-5 parts of purified tara gum, 18-22 parts of amide monomers, 5-8 parts of initiator and 480-520 parts of precipitant, based on the weight parts of the raw materials for preparing the binder.

[0037] In a further embodiment, the amide monomer is one or more of acrylamide, bisolefin amide, polyether-polyacrylamide. Preferably, the amide monomer is acrylamide, see Figure 2 The structural formula of acrylamide is shown.

[0038] In a further embodiment, the initiator is one or more of ammonium cerium nitrate and benzoyl peroxide.

[0039] In a further embodiment, the precipitant is one or more of anhydrous ethanol, isopropanol, acetone, and ethyl acetate.

[0040] In a further embodiment, the binder further includes a solvent, and the solvent is one or more of deionized water, benzyl acetate, hexyl butyrate, toluene, xylene, isobutyl isobutyrate, and butyl butyrate.

[0041] The second aspect of the present invention provides a method for preparing a binder, the method comprising the following steps: S1. Tara gum is directly purified to obtain a colloidal substance, and then a rotary evaporator is used to remove the extractant to obtain pure Tara gum, i.e., binder A; S2, 4g of binder A and 150g of deionized water were added to a 250mL four-necked flask, nitrogen was introduced as a protective gas, and the mixture was stirred at room temperature for 5h to fully dissolve the binder A to obtain a tara gum solution; 20g of acrylamide monomer was dissolved in 30g of deionized water and then added dropwise to the tara gum solution, and the mixture was stirred for 1h to cause a graft copolymerization reaction between the binder A and the tara gum solution to obtain a polymer solution; S3, take 6g of ammonium cerium nitrate and dissolve it in 25g of water to prepare an initiator, and drip the initiator into the above polymer solution, and the dripping rate of the initiator is controlled within 5mL / min; after the dripping of the initiator is completed, place it in a 40-50℃ water bath to react for 10-14h to obtain a reaction solution; generally, place it in a 45℃ water bath to react for 12h; S4. After the reaction is completed, the reaction solution is taken out, 500 mL of anhydrous ethanol is added to precipitate a solid, and the obtained solid product is washed with anhydrous ethanol for multiple times and then vacuum dried; preferably, the vacuum drying temperature is 50° C., and the drying time is 12 h. The obtained solid product is the binder provided by the present invention, namely, binder B.

[0042] Preferably, the extractant is one or more of anhydrous ethanol, methanol or isopropanol.

[0043] The third aspect of the present invention provides a negative electrode slurry, including a negative electrode active material, silicon dioxide or silicon carbon powder, a conductive agent, CMC (2% glue) and the binder disclosed in the present invention.

[0044] In a further solution, the mass ratio of the negative electrode active material, silicon oxide or silicon carbon powder, conductive agent, CMC (2% gel solution), and binder is (89.09-95.8): (5.27-6.71): 1.5: 0.5: 2.2.

[0045] A fourth aspect of the present invention provides a negative electrode plate, which is made of a current collector and the above-mentioned negative electrode slurry loaded on the current collector.

[0046] A fifth aspect of the present invention provides an ion battery, comprising a positive electrode plate and the above-mentioned negative electrode plate.

[0047] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0048] Example 1 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: conductive agent: CMC (2% glue): binder A = 95.8:1.5:0.5:2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 55%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive; finally, the button cell is subjected to a constant current charge and discharge test.

[0049] Example 2 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: silicon dioxide: conductive agent: CMC (2% glue): binder A = 89.09: 6.71: 1.5: 0.5: 2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive; finally, the button cell is subjected to a constant current charge and discharge test.

[0050] Example 3 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: silicon carbon powder: conductive agent: CMC (2% glue): binder A = 90.53: 5.27: 1.5: 0.5: 2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additives; finally, the button cell is subjected to a constant current charge and discharge test.

[0051] Example 4 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: conductive agent: CMC (2% glue): binder B = 95.8:1.5:0.5:2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 55%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additives; finally, the button cell is subjected to a constant current charge and discharge test.

[0052] Example 5 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: silicon dioxide: conductive agent: CMC (2% glue): binder B = 89.09: 6.71: 1.5: 0.5: 2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive; finally, the button cell is subjected to a constant current charge and discharge test.

[0053] Example 6 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: silicon carbon powder: conductive agent: CMC (2% glue): binder B = 90.53: 5.27: 1.5: 0.5: 2.2, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additives; finally, the button cell is subjected to a constant current charge and discharge test.

[0054] Comparative Example 1 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery - graphite: conductive agent: CMC (2% glue): SBR (40% solid content) = 95.8:1.5:1.2:1.5, the composition is dispersed in appropriate deionized water, the solid content is maintained at 55%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein: the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive; finally, the button cell is subjected to a constant current charge and discharge test.

[0055] Comparative Example 2 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery, graphite: silicon dioxide: conductive agent: CMC (2% gel): SBR (40% solid content) = 89.09: 6.71: 1.5: 1.2: 1.5, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein: the electrolyte is a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive; finally, the button cell is subjected to a constant current charge and discharge test.

[0056] Comparative Example 3 In terms of mass percentage, in the negative electrode sheet of the lithium-ion battery, graphite: silicon carbon powder: conductive agent: CMC (2% glue): SBR (40% solid content) = 90.53: 5.27: 1.5: 1.2: 1.5, the composition is dispersed in appropriate deionized water, the solid content is maintained at 52%, and stirred for 12 hours; the mixed slurry is evenly coated on a copper foil, and dried at 80°C for 12 hours under vacuum conditions to obtain a negative electrode sheet; after drying, the sheet is cut and transferred to a glove box, and the lithium sheet is used as the counter electrode to assemble into a 2032 button cell, wherein: the electrolyte is a PC / EC (volume ratio of 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additives; finally, the button cell is subjected to a constant current charge and discharge test.

[0057] The following are the results of constant current charge and discharge tests on the button cells in the above Examples 1-6 and Comparative Examples 1-3:

[0058] It can be seen from the above table that the button cell of Example 6 has the best cell cycle performance, that is, the binder B provided by the present invention has good viscosity and can better restrain the displacement and fragmentation tendency of the active material; at the same time, the total amount of binder can be reduced on the original basis.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A binder, characterized in that: The binder is applied to lithium-ion batteries, and the raw material of the binder is tara gum.

2. The adhesive according to claim 1, characterized in that The binder is prepared by copolymerization of tara gum and amide monomers under the initiation of an initiator.

3. The adhesive according to claim 2, characterized in that Calculated by weight of the raw materials for preparing the binder, the raw materials of the compound include 3-5 parts of tara gum, 18-22 parts of amide monomers, 5-8 parts of initiators and 480-520 parts of precipitants.

4. The adhesive according to claim 3, characterized in that The amide monomer is one or more of acrylamide, bisolefin amide, polyether-polyacrylamide; And / or, the initiator is one or more of ammonium cerium nitrate and benzoyl peroxide; And / or, the precipitant is one or more of anhydrous ethanol, isopropanol, acetone, and ethyl acetate; And / or, the binder further comprises a solvent, and the solvent is one or more of deionized water, benzyl acetate, hexyl butyrate, toluene, xylene, isobutyl isobutyrate, and butyl butyrate.

5. The method for preparing the binder according to any one of claims 2 to 4, characterized in that: The preparation method comprises the following steps: S1. Take purified tara gum to obtain binder A; S2, preparing the binder A into a first solution, mixing it with the amide monomer to carry out graft copolymerization reaction, and obtaining a second solution; S3, adding the initiator dropwise into the second solution at a rate of up to 5 mL / min to obtain a third solution; S4. Adding a precipitant to the third solution to obtain a solid product, washing and drying the solid product to obtain the binder.

6. The method for preparing the adhesive according to claim 5, characterized in that: The step S3 further comprises placing the solution after the initiator has been dripped in a water bath at 40-50° C. to react for 10-14 hours.

7. The method for preparing the adhesive according to claim 5, characterized in that: The purified tara gum is obtained by extraction, wherein the extractant used in the extraction is one or more of anhydrous ethanol, methanol or isopropanol.

8. The method for preparing the adhesive according to claim 7, characterized in that: The step of adding the precipitant to the third solution to obtain a solid product further comprises: adding the precipitant into the third solution to extract the synthetic product, so as to leave the synthetic product in the precipitant layer; The extractant was removed using a rotary evaporator to obtain the solid product.

9. A negative electrode slurry, characterized in that: The invention comprises a negative electrode active material, a conductive agent and the binder according to any one of claims 1 to 7.

10. The negative electrode slurry according to claim 9, characterized in that: It also includes silicon dioxide or silicon carbon powder, CMC (2% glue), among which: The mass ratio of the negative electrode active material, the silicon oxide or silicon carbon powder, the conductive agent, the CMC (2% glue solution), and the binder is (89.09-95.8): (5.27-6.71): 1.5: 0.5: 2.

2.

11. A negative electrode plate, characterized in that: The negative electrode sheet is made of a current collector and the negative electrode slurry according to any one of claims 9 to 10 loaded on the current collector.

12. A lithium ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet as claimed in claim 11.